Increase wearproofness of steel cylindrical details by discrete electromechanical strengthening - Dykha, Aleksandr; Dykha, Maksym (International Journal of Engineering and Technology, 2019)
On the basis of theoretical and experimental researches tribotechnology of the discrete electromechanics strengthening has been offered for the increase of wearproofness of steel details. The new way of discrete electromechanical treatment has been developed. Analytical dependences and numeral models have been received for determination of contact descriptions at co-operation of instrument and detail for the electromechanics strengthening. By the method of finite elements the conducted analysis tensely deformed to the state of surface after its treatment by discrete electromechanics treatment with different geometrical layout of the locally fixed areas charts. The developed criteria of choice of optimum geometry of the discrete strengthening are on the basis of minimization of level of tensions in a superficial layer. For prognostication of wearproofness the model of wear and method of determination of descriptions of wear as a result of experimental tests have been developed. For the analysis of influence of the tensely deformed state of discrete surface on wearproofness the experimental tests at the discrete electromechanical strengthening have been conducted.
Keywords: Electromechanics Strengthening; Wearproofness; Tensely Deformed State; Discrete Surface; Wear Test.